Study of PVA-GTA Fricke Gel Dosimeters Exposed to 60Co Source Using Magnetic Resonance Imaging - E. Edalatkhah; P. Rezaeian (Journal of Nuclear Research and Applications, 2023)
This study was conducted to evaluate the response of PVA Fricke gel dosimeters by two different methods, optical spectroscopy and magnetic resonance imaging. At first, samples of PVA Fricke xylenol orange gel dosimeters were prepared in our laboratory. Then, the samples were irradiated up to 25 Gy by gamma rays. Finally, studies on the optical absorbance and magnetic resonance of the prepared Fricke gel dosimeters were carried out. Optical absorbance measurements of the samples were performed with a spectrophotometer. Magnetic resonance measurements of the gel dosimeters were carried out by means of a 1.5 T scanner. Radiation induced oxidation of ferrous ions with the yield proportional to absorbed dose was observed. The dosimeters were found to offer good linearity in the range of 0-15 Gy. MRI scans of the dosimeters also showed that the longitudinal relaxation time is dose dependent. The findings suggest PVA Fricke gel dosimeters as a dosimetric tool for medical applications like radiation therapy.